2016
DOI: 10.1016/s1525-0016(16)33257-9
|View full text |Cite
|
Sign up to set email alerts
|

448. Therapeutic Angiogenesis by Subcutaneous Cell Sheet Delivery Is Superior to Cell Injection: A Study of ADSC Efficacy in a Model of Hind Limb Ischemia

Abstract: NICD and activated expression of Notch target genes (Hes, Hey). Activation of Notch signaling upregulated expression of endothelial cell transcription factors Gata 4 and Vezf1 in CSCs but γ-secretase inhibitor prevented Notch signaling activation and endothelial cell commitment of CSCs. CONCLUSIONS: These results revealed that Notch signaling activation promote CSCs commitment toward vascular cells. These findings suggest that modulation of Notch signaling can be promising therapeutic strategy for the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…[ 25 ] In synergy with other cells, they recover damaged cells and promote the formation of new functional tissues. [ 25 26 ] Studies have also shown that ADSCs are usually placed as seed cells to produce biologically vital factors in engineered tissue constructs. A series of growth factors secreted by ADSCs are thought to be associated with their stimulating effects.…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 ] In synergy with other cells, they recover damaged cells and promote the formation of new functional tissues. [ 25 26 ] Studies have also shown that ADSCs are usually placed as seed cells to produce biologically vital factors in engineered tissue constructs. A series of growth factors secreted by ADSCs are thought to be associated with their stimulating effects.…”
Section: Discussionmentioning
confidence: 99%